Alternative for Germany: Germany's new right‐wing extremists. (19th November 2018) - Klikauer, Thomas
Abstract : In September 2017, a new political party entered Germany's parliament harvesting anti‐establishment feelings while converting frustrations over neoliberalism into xenophobia and racism. The new party calls itself "Alternative for Germany" (AfD). Corporate media label the party "populist" and "right wing." This commentary argues that the party has clear Nazi tendencies. Originally founded as a pro‐capitalism, pro‐neoliberalism, anti‐Europe, and nationalistic party, the AfD shows very serious tendencies toward Nazism. Its recent party convention moved the party even more toward Nazism. The party's Nazism is signified in the use of AfD terminologies such as the so‐far taboo‐word "völkisch"—a Nazi‐word not used in post‐war Germany. It means an anti‐Semitic Aryan Volk that is ethnically cleansed to establish the mythical Germanic and deeply antidemocratic Volksgemeinschaft led by an authoritarian leader, the Führer. Under the camouflage of being "right wing, " a slow mainstreaming of fascism occurs. This commentary has four parts: the introduction explains the AfD's historic origins and predecessors; the second part elucidates media support; the third part discusses populism; and the fourth part shows the party's support network. The commentary ends with a short conclusion. Using secondary and German‐language sources, the commentary documents the AfD‐Nazi link based on statements made by AfD members and leaders. This article concludes that the AfD might indeed be called Germany's new Nazis.